Robot-assisted fracture fixation for pelvic fractures: a scoping review of emerging technologies - Wu, Boyi; Wang, Gengqi; Zheng, Jun (Frontiers in Surgery, 2025)
BackgroundPelvic fractures (PF) are complex injuries often requiring multidisciplinary management. Robot-assisted fracture Fixation (RAFF) systems have emerged as a promising innovation in PF treatment, offering improved precision, reduced radiation exposure, and minimally invasive techniques. This scoping review aims to synthesize the current evidence on the accuracy, safety, and efficiency of RAFF systems in managing PF, highlighting their benefits, limitations, and future potential.MethodsA scoping review was conducted adhering to PRISMA-ScR guidelines. Databases including PubMed and Web of Science were searched to identify studies evaluating RAFF systems for PF. Eligible studies involved adult patients undergoing robot-assisted interventions for PF and reported outcomes on accuracy, operative time, blood loss, and complications. Data extraction focused on study design, robotic platform, outcomes, and methodological quality assessed via MINORS and RoB-2.ResultsTwelve studies were included, comprising case reports, case series, and one comparative study. RAFF systems demonstrated high accuracy in fracture reduction with reduced fluoroscopic exposure and minimal blood loss. Functional outcomes assessed by Matta criteria and Majeed scores were favorable. However, most studies were limited by small sample sizes and lack of long-term follow-up. No high-quality randomized controlled trials were identified.ConclusionsRAFF systems show significant potential in improving surgical outcomes for PF, offering enhanced precision and reduced operative risks. Nevertheless, robust, high-quality studies are needed to establish the long-term efficacy and economic viability of these systems. Standardized protocols and multicenter trials are critical for advancing the application of robotics in orthopedic trauma surgery.